Modelling success networks to improve the quality of undergraduate education. Issue 2 (4th May 2017) - Woolcott, Geoff; Keast, Robyn; Chamberlain, Daniel; Farr-Wharton, Ben
Abstract: Discussions of support and intervention in undergraduate university education are dominated by discussion of attrition. This study quests more broadly in arguing that support and intervention for undergraduate students may also benefit from models of engagement and success as well as conventional risk and failure. Supporting this proposition is a study that involved multifactorial approaches based in a combination of aspects of social network theory and social ecology theory. Analysis was enacted through social network analysis of archival data sets derived from a single cohort of 4065 undergraduate students at a regional Australian university. The findings suggest that models of academic success are suited to examination of the broader issues of student agency and undergraduate university education. The success networks developed are uniquely student-centred and place-based and may serve as more nuanced models for university intervention and support structures and mechanisms.